Effect of iontophoretic 5-HT on raphe-spinal neurons - ZHU Li-xia; LI Chun-yuan; SHI Qing-yao; JI Chang-fu (Acta Pharmacologica Sinica, 2016)
Forty-four raphe-spinal neurons in the nucleus raphe magnus (NRM) of immobilized rats were identified by antidromic action potentials with constant latency, ability of following high frequency stimulation (333 Hz) and collision by orthodromi caction potentials or spontaneous spikes. The spontaneous discharges were reduced by iontophoretic 5-HT in all 16 raphe-spinal neurons tested and both spontaneous discharges and excitatory effect of acupuncture were inhibited by lysergic acid diethylamide (LSD) 10 micrg/kg in all 9 neurons. These inhibitory effect may be mediated by presynaptic negative feedback regulation. Therefore, it is considered that these neurons may be serotonergic. Most serotonergic raphe-spinal neurons may be activated by acupuncture, which may play an important role in acupuncture analgesia.